Sensitivity of the Kaiser Permanente early-onset sepsis calculator: A systematic review and meta-analysis - Katherine J. Pettinger; Katie Mayers; Liz McKechnie; Bob Phillips (EClinicalMedicine, 2020)
Summary: Background: Determining which babies should receive antibiotics for potential early onset sepsis (EOS) is challenging. We performed a meta-analysis quantifying how many EOS cases might be ‘missed’ using the Kaiser Permanente electronic calculator, compared with National Institute for Health and Care Excellence (NICE) guidelines. Methods: A systematic literature search was carried out for studies citing the article in which the calculator was publicised. Studies were eligible if they presented data evaluating the calculator, either by retrospective case review or prospective cohort study. The primary outcome measure was numbers of culture positive EOS cases where the calculator did not recommend empirical antibiotics, but NICE guidelines would have. Data were pooled using a random effect meta-analysis. A subgroup analysis was performed using data from studies of babies exposed to chorioamnionitis. Findings: Eleven studies were included. There were a total of 75 EOS cases across the studies and a minimum of 14 (best case scenario), and a maximum of 22 (worst case scenario) cases where use of the calculator would have resulted in delayed or missed treatment, compared to if NICE guidelines had been followed. The probability of missed/delayed treatment for an EOS case were best case 0.19 [95% confidence intervals 0.11 – 0.29], worst case 0.31 [95% CI 0.17 – 0.49]. The probability of missing cases was significantly more in babies exposed to chorioamnionitis Interpretation: A large proportion of EOS cases were ‘missed’ by the calculator. Further evaluation of the calculator is recommended before it is introduced into UK clinical practice. Funding: None. Keywords: Early onset sepsis, Neonatal sepsis, Risk calculator, Systematic review, Diagnostic test accuracy